2002
DOI: 10.1177/112067210201200101
|View full text |Cite|
|
Sign up to set email alerts
|

Prevalence of Astigmatism among Students in Northern Greece

Abstract: There is considerable variability in the prevalence of astigmatism worldwide, as indicated by different studies. However, this refractive error prevails at low levels in the Greek student population, compared with other countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 15 publications
(9 reference statements)
0
6
0
Order By: Relevance
“…7 Previous studies have reported that the risk of developing astigmatism doubles in first-degree relatives of individuals with astigmatism. [8][9][10] Family and twin studies have determined a broad sense heritability of approximately 60%, 2,11,12 which suggests a significant genetic contribution to astigmatism.…”
Section: Resultsmentioning
confidence: 99%
“…7 Previous studies have reported that the risk of developing astigmatism doubles in first-degree relatives of individuals with astigmatism. [8][9][10] Family and twin studies have determined a broad sense heritability of approximately 60%, 2,11,12 which suggests a significant genetic contribution to astigmatism.…”
Section: Resultsmentioning
confidence: 99%
“…The prevalence of ametropias of 71% for hyperopia, 13.3% for myopia and 34% for astigmatism corroborates the national literature, but disagrees with international publications, mainly from the Orient, where myopia is always considered to be the most common refractive error in students (3,(5)(6)(7)(8)(10)(11)(12)(13)(14)(15)(16) . Some studies cite severe myopia with a prevalence of 24 to 41%, disagreeing with this study, in which it is approximately 2% (5) .…”
Section: Discussionmentioning
confidence: 57%
“…Few data concerning astigmatism axis were found, as well as in respect to association between both axes. A majority comment on the type of astigmatism (whether myopic, hyperopic or mixed) (4,(11)(12)17) . What can be observed is that the great majority (77.5%) is in the group in with-the-rule, corroborating results by Alves (2,18) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Another study on astigmatism among 1738 Greek students (aged 15-18 years) reported prevalence rates of 10.2 percent. 9 This study benefited from the fact that there was a high participation rate (97.3%) although the overall sample size was…”
Section: Discussionmentioning
confidence: 99%